The intangible economy and firm superior performance: evidence from Australia - Galbreath, Jeremy (MGSM, 2005)
Scholars suggest that in the 'intangible' economy, firms need to exploit intangible, rather than tangible resources to generate superior performance. In this study, we theoretically developed the proposition that intangible assets and capabilities would be linked to superior performance while tangible assets would be linked to low performance. Drawing upon a broad sample of manufacturing and services firms in Australia and by segmenting out the central cluster of firms, we found that tangible resources were linked to low performance while as hypothesised, intangible assets and capabilities were linked to superior performance. Studies such as the present one offer some support for resourcebased theory which argues that in today's economy, resources that are intangible in nature are more likely to be sources of competitive advantage than resources that are tangible in nature.